PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP MANAJEMEN STRES SISWA KELAS X MIA SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2014/2015 - Chelry Indra Indra; Tri Umari Umari; Zulfan Saam Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on the observation of many phenomena that occur at school, such as: many students who complain when given a task by their teachers, some of them will stay in the classroom and the others go out of classroom while teaching process is running, lack of motivation to learn because of the condition of the class is not fun. This resulted in many students stress, and can disturbing students focus. Stress management is a program for controlling or setting the stress which aims to recognize the causes of stress and know the techniques to manage stress, so that can make people better. Guidance group is one of the services to help students solve the problem, therefore researchers interested in studying the effect of group counseling services for stress management students. This type of research used in this study was pre-experimental with one group pre-test post-test. Subjects in this study were 30 students who had stress management in the medium category. Based on the analysis of obtained is bigger than t table, means (13.86> 2,000). Thus Ho is rejected and Ha accepted, which means that in this study there are significant differences of increasingstudentsstress management before and after the given group counseling services. Based on the correlation of test results it finds 0.7 and determinant coefficient is r2 0.49, therefore the influence of counseling services for stress students management group is 49%. If compared with r table to dk 58 with the standard error of 5% means (0.49> 0.361), thereby Ha accepted and there is a significant positive effect of group counseling services for stress management students. Keywords: Guidance group, Stress management